‘Constitutional Unconstitutionality’: Constitutional Review of the COVID-19 Restrictions on Fundamental Rights in Slovenia - Flander, Benjamin (Law, Identity and Values, 2022)
The article addresses some of the most important decisions of the Slovenian Constitutional Court related to the COVID-19 restrictions on fundamental rights. By taking a close look at the case law of the Constitutional Court, the author aims at presenting to the foreign readers and the international professional audience the specific features and peculiarities of the constitutional judicial discourse on the COVID-19 measures in Slovenia that has so far proved to be extremely controversial. While in the early stages of the COVID-19 crisis, the Slovenian Constitutional Court found the restriction of movement outside the municipality of one’s residence in line with the Constitution, it later ruled that the government ordinances introducing the restrictions of fundamental rights were unconstitutional in several cases. In most of these cases, however, the reason for this was not the unconstitutionality of the measures themselves, but the unconstitutionality of their statutory legal basis. The overview revealed, inter alia, that since the outbreak of the epidemic, the Constitutional Court has issued certain important and groundbreaking decisions on the one hand, and made some good and less good compromises on the other.